Artur vai à guerra: a memória de um febiano perenizada em linguagem fílmica - Schmitz, Anderson Iura Amaral (2011)
This paper is a case study involving the documentary Artur Melo da Costa: missionary hero. The objective was to examine whether it is possible for a person turn into hero through its exposure from the film image. To flesh out the research was necessary to use oral history, literature review and empiricism. The text makes an original theoretical approach, where many works are analyzed, so we make allowances for the case study. In order to understand the process of heroicização was made a biography of Arthur Melo da Costa, who is the central object of our study. We also did an analysis on all the events that marked the construction process of the documentary, so that we can understand if, in fact, there was turn into hero Artur Melo da Costa in the community of São Luiz Gonzaga, Rio Grande do Sul. The research provides new information relevant to the community in question, so that we can understand that the construction of history is made everyday. Finally, the work serves as a reference for you to understand is how to make themselves a hero through the construction of filmic language, this case of a documentary.